On the Characteristic Operators and Projections and on the Solutions of Weyl Type of Dissipative and Accumulative Operator Systems. I. General Case - Khrabustovsky, V. I. (Журнал математичної фізики, аналізу, геометрії, 2006)
In the context of dissipative and accumulative differential equations (which contain the spectral parameter $λ$ nonlinearly) in a separable Hilbert space $\mathcal{H}$ we introduce a characteristic operator $M(λ)$ that works as an analog of the characteristic Weyl-Titchmarsh matrix. Its existence and properties are investigated. A description of $M(λ)$ that corresponds to separated boundary conditions is given. Analogs for Weyl functions and solutions are introduced. Weyl type inequalities for those analogs are established, which reduce to well-known inequalities in various special cases. The proofs are based on description and properties of maximal semi-definite subspaces in $\mathcal{H}^2$ of special form that we provide while studying boundary problems for equations as above. Mathematics Subject Classification: 34A55, 34G10, 47E05.